Indoor concentrations of VOCs in beauty salons; association with cosmetic practices and health risk assessment - Hadei, Mostafa (J Occup Med Toxicol, 2018)
BACKGROUND: The use of cosmetic products in beauty salons emits numerous kinds of toxic air pollutants. The objectives of this study were to measure the concentrations of benzene, toluene, ethylbenzene, xylene, formaldehyde, and acetaldehyde in 20 large beauty salons in Tehran and relate the observed concentrations to environmental and occupational characteristics of the salons. METHODS: Samples were collected from inside and outside air of 20 selected salons located in different areas of the city. Several additional parameters were recorded during the sampling process including surface area, number of active employees, type of ventilation, type of ongoing treatments, temperature, humidity. Deterministic and stochastic health risk assessment of the compounds were performed. RESULTS: Indoor concentrations of each pollutant were significantly higher than its outdoor concentrations. Health risk assessment showed that benzene, formaldehyde and acetaldehyde represent a possible cancer risk in the beauty salons. In addition, toluene, ethylbenzene, and xylene had negligible non-carcinogenic risks. Ventilation with air purifier, and fan with open window were more effective than using just a fan. Concentrations of benzene and toluene were affected by the number of hair dying treatments. The concentration of xylene was affected by the number of hair styling. The concentration of formaldehyde was affected by the number of hair styling and number of nail treatments. CONCLUSION: With improved ventilation and requirements for reformulated cosmetic, concentrations of toxic air pollutants in beauty salons could be reduced. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12995-018-0213-x) contains supplementary material, which is available to authorized users.